Lyophilized autologous serum stabilized with sucrose promotes the proliferation and migration of keratinocyte - Iman Permana Maksum, Siti Jubaedah, Yosua Yosua, Rostina Melpin, Mervina Rondonowu, Sutarya Enus&, Saadah Diana Rachman, Sriwidodo Sriwidodo, Toto Subroto (Journal of Applied Pharmaceutical Science, 2021)
The autologous serum is widely used as therapy for epithelial cell treatment and dry eye syndrome due to its epitheliotropic properties, which are similar to tears. The serum contains human epidermal growth factor (hEGF) and retinol, which play important roles in cell proliferation and differentiation. Freeze-drying improves the stability of therapeutic proteins for long-term storage. Sucrose is known to stabilize protein during freeze-drying and storage. Also, antioxidants such as vitamin E can maintain unstable retinol levels. This study aims to investigate the effect of the addition of sucrose to preserve dried autologous serum during freeze-drying and storage, as well as the effects of the serum on keratinocyte proliferation and migration. The addition of sucrose to autologous serum could preserve the dried autologous serum components above the minimum requirement for substitute tears after 6 months of storage. The highest cell proliferation was achieved by the addition of 25 ng/ml hEGF and 1% vitamin E, while the highest migration activity was achieved by the addition of 25 ng/ml hEGF. Freeze-drying autologous serum with the addition of sucrose and storage at low temperatures can extend its shelf life. Also, the addition of exogenous hEGF and vitamin E to autologous serum can increase the proliferation and migration of keratinocyte cells.
Keywords: Autologous serum, cell proliferation and migration, freeze-drying, hEGF, sucrose, vitamin E.